Does the European Union Walk on the Path of Sustainability? - Orloczki, Mónika (Theory, Methodology, Practice – Review of Business and Management, 2013)
Nowadays more than 100 countries try to implement a national sustainable development strategy with hundreds of indicators in use for the evaluation of their progress. The aim of the article is to compare the sustainable development performances of the EU-27 countries through some critical indicators chosen from the Sustainable Development Indicator (SDI) set of Eurostat.